Identification of the Unwinding Region in the Clostridioides difficile Chromosomal Origin of Replication - Oliveira Paiva, Ana M.; van Eijk, Erika; Friggen, Annemieke H.; Weigel, Christoph; Smits, Wiep Klaas (Frontiers in Microbiology, 2020)
Faithful DNA replication is crucial for viability of cells across all kingdoms. Targeting DNA replication is a viable strategy for inhibition of bacterial pathogens. Clostridioides difficile is an important enteropathogen that causes potentially fatal intestinal inflammation. Knowledge about DNA replication in this organism is limited and no data is available on the very first steps of DNA replication. Here, we use a combination of in silico predictions and in vitro experiments to demonstrate that C. difficile employs a bipartite origin of replication that shows DnaA-dependent melting at oriC2, located in the dnaA-dnaN intergenic region. Analysis of putative origins of replication in different clostridia suggests that the main features of the origin architecture are conserved. This study is the first to characterize aspects of the origin region of C. difficile and contributes to our understanding of the initiation of DNA replication in clostridia.